2022
DOI: 10.3390/insects13100867
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Functional Characterization of a Soluble Trehalase in Lissorhoptrus oryzophilus (Coleoptera: Curculionidae)

Abstract: Trehalase is the only enzyme known for the irreversible splitting of trehalose and plays a major role in insect growth and development. In this report, we describe a basic study of the trehalase gene fragment encoding a soluble trehalase from Lissorhoptrus oryzophilus (LoTRE1). Sequence alignment and phylogenetic analysis suggested that LoTRE1 was similar to some known insect trehalases and belongs to the Coleoptera trehalase group. Additionally, LoTRE1 was expressed mainly in the fat body. Purified protein wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The introduction efficiency was affected by the methods, species, age, and other factors. , Compared with other methods, orally delivered RNAi has great advantages, which avoids unknown injuries caused by injection. It is also a suitable method for RWW, as the interference efficiency of RWW trehalase gene LoTRE1 reduced the expression levels to 40% at 24 h and 56% at 48 h in our previous study . The antennal response of LoryOR20-silenced RWWs showed an extremely significant difference from that of the wild-type RWWs, which not only showed that in RWW the feeding method for RNAi ORs was effective but also indicated that LoryOR20 was the main and even the only PAA receptor.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The introduction efficiency was affected by the methods, species, age, and other factors. , Compared with other methods, orally delivered RNAi has great advantages, which avoids unknown injuries caused by injection. It is also a suitable method for RWW, as the interference efficiency of RWW trehalase gene LoTRE1 reduced the expression levels to 40% at 24 h and 56% at 48 h in our previous study . The antennal response of LoryOR20-silenced RWWs showed an extremely significant difference from that of the wild-type RWWs, which not only showed that in RWW the feeding method for RNAi ORs was effective but also indicated that LoryOR20 was the main and even the only PAA receptor.…”
Section: Discussionmentioning
confidence: 71%
“…It is also a suitable method for RWW, as the interference efficiency of RWW trehalase gene LoTRE1 reduced the expression levels to 40% at 24 h and 56% at 48 h in our previous study. 49 The antennal response of LoryOR20silenced RWWs showed an extremely significant difference from that of the wild-type RWWs, which not only showed that in RWW the feeding method for RNAi ORs was effective but also indicated that LoryOR20 was the main and even the only PAA receptor. As RNAi-based pesticides have exhibited a good prospect in crop pests' suppression, dsRNA-LoryOR20 may be used as an effective component to control RWWs by interfering with host localization.…”
Section: Discussionmentioning
confidence: 95%
“…RNAi can induce targeted gene silencing, and it has successfully been used for evaluating functional genes in various insects [ 55 , 56 , 57 , 58 , 59 , 60 ]. Previous studies have shown that in S. exigua , the knockdown of SeTre1 and SeTre2 increases the mortality and abnormality rates and significantly decreases CHS expression levels and chitin content [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the total RNA extraction and cDNA synthesis, we followed the same method as described in a previous study [43]. Total RNA was extracted from the whole bodies of three L. oryzophilus adults using RNAiso Plus (Takara, Dalian, China), following the manufacturer's instructions.…”
Section: Sequence Determination and Bioinformatics Analysis Of Tps Genementioning
confidence: 99%